Effectiveness of mind-body intervention on oocyte quality and serum cortisol level in sub-fertile women undergoing IVF treatment in Wardha region: A Study Protocol (Journal of Pharmaceutical Negative Results, 2022)
In last 4 decades, the treatment of infertility has changed fundamentally and has been used increasingly in the whole world. Fresh embryo transfer and vitrified thawed embryo transfer are the two methods that are preferred. Nowadays, freeze all cycles are much more involved in the treatment of infertility. Maternal complications are found to be lesser in pregnancy arising from the cryopreserved thawed embryo transfers. Women undergoing frozen embryo transfer are found to have good ovarian reserve with a lower risk of preterm birth. But the occurrence of pregnancy-induced hypertension syndrome is found to be more in cryopreserved embryo transfer than in fresh embryo transfer. The ovarian hyperstimulation syndrome is found to be same in both types of embryo transfers. Objective of the study is to correlate the β-HCG outcome of fresh and frozen embryo shifting, to correlate pregnancy complications in patients with fresh and frozen embryo shifting, to identify various reasons for pregnancy complications and to establish criteria for selection of embryo transfer type (Fresh/Frozen). This invasive methodology includes a recording of the treatment history and the indications. Counseling of all the participants for research will be done. The further protocol includes evaluation of outcomes of both the techniques by comparing its complications in pregnancy.